Impact of urban expansion on ecosystem service values in Debre Markos town and surrounding Peri-Urban areas, Northwestern Ethiopia, using geospatial technology and remote sensing - Yedem Fentie, Ayalneh; Ayenew Gebeyehu, Lakachew; Dagnaw Mekonnen, Addisu (Ecological Questions, 2026)
Urban expansion in peri-urban areas significantly impacts ecosystem service functions by converting land use/land cover (LULC) types to built-up areas. LULC changes resulting from urban expansion can affect ecosystem service functions. Therefore, the objective of this study was to assess the impact of urban expansion on ecosystem service values (ESV) in the town of Debre Markos and its peri-urban areas. To this end, the spatial and temporal dynamics of LULC were analysed using Landsat 7 and 8 (ETM+ and OLI) satellite images from the last 20 years. ESVs were generated for each LULC category using ERDAS IMAGINE 2015 and ArcGIS 10.6. Based on the study results, the urban settlement in the study area increased by 1360 ha (285.94%), while the area of other LULC types decreased. As a result of urban expansion in the study area over the last 20 years (2004–2024), there has been a 19.33% decline in total ESVs. This indicates that the study area has suffered a loss of USD 0.683 million/ha/year due to LULC change caused by urban expansion. The LULC changes resulting from urbanisation in the area have therefore negatively impacted ecosystem service functions over the last 20 years. Consequently, proper planning of urban expansion and conservation of natural resources (inland wetlands and forests, including plantations) are necessary for sustainable ecosystem management in the area.